Antifungal and antibacterial activities of Usnea lichen extracts and associated Endolichenic fungi from the Western Ghats, India - Antony, Georgy; Bhaskar, Anusha; M., Sudheesh; R., Manikkumar (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Lichens of the Usnea genus and their associated Endolichenic fungi from biodiversity hotspots like the Western Ghats, India, represent underexplored sources of secondary metabolites with antimicrobial potential. This study evaluates the antifungal activity of Usnea extracts and antibacterial efficacy of Endolichenic fungi to address the surge in antimicrobial resistance, demanding novel bioactive agents. Methods: Usnea species (U. subsordiata, U. perplexans, U. spinocula, U. undulata, U. maculata) were collected from Kodayar, Tamil Nadu and extracted sequentially with methanol, acetone and diethyl ether. Antifungal minimum inhibitory concentrations were determined by performing broth macrodilution against Aspergillus niger, A. flavus, Fusarium oxysporum, and F. solani. ELF were isolated from U. perplexans thalli, cultured and their ethyl acetate extracts tested for antibacterial activity using agar well diffusion against Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumoniae and Escherichia coli. Results: U. subsordiata extracts exhibited the strongest antifungal activity (MICs 93.72–109.34 µg/ml), while U. maculata showed the weakest (234.375–531.25 µg/ml). ELF isolates (Acremonium lichenicola, Aspergillus spp., Fusarium spp., Penicillium spp.) demonstrated broad-spectrum antibacterial effects, with Aspergillus spp. yielding the largest zones of inhibition, particularly against Gram-positive bacteria. Significant variations were confirmed by two-way ANOVA (p<0.001). Conclusions: Usnea lichens and ELF harbor potent antimicrobial compounds, offering viable alternatives against antimicrobial resistant pathogens and emphasising the need for conservation and further metabolite characterization.